ANALISIS PENGARUH PROJECT COST MANAGEMENT DAN STANDARD MARKUP PRICING SEBAGAI STRATEGI BERKEMBANG BUKIT GRHADIKA GARDEN AGRO EDUWISATA DI MASA PANDEMI - Indra Trisna Septiawan; Endang Kartini Panggiarti (Transpublika Publisher, 2022)
This study aims to assess the approach employed by the research object, namely Bukit Grhadika Garden Agro Eduwisata, in order to survive the pandemic. This is a qualitative study employing a descriptive approach. Interviews with study subjects are used to elicit reliable and accurate information, which is supplemented by secondary data. This research examines the effect of Project Cost Management and Standard Markup Pricing strategies on cost reductions necessary to survive the pandemic. The findings revealed that the measures employed, namely Project Cost Management and Standard Markup Pricing, had a positive influence in the development of Bukit Grhadika Garden Agro Eduwisata during the pandemic. The Project Cost Management strategy used to develop Agro Edutourism has a significant impact on the development and improvement of tourist attractions that are more appealing to potential visitors, even during a pandemic. In addition, tourism marketing via online media is quite attractive and helps increase the number of tourists. Additionally, Standard Markup Pricing increases visitor interest as well. This study finds that the management of Bukit Grhadika Garden Agro Eduwisata's business strategy enabled the company to survive the pandemic